Kombinasi Kompresi Huffman Coding dan Teknik Least Significant Bit untuk Efisiensi dan Keamanan Penyembunyian Data - Riska Amelia Puspita Sari; Iin Nurul Latifah Nurul Latifah; Maisie Elviana; Dimas Febriawan (The Indonesian Journal of Computer Science, 2026)
The rapid advancement of digital technology requires stronger data protection mechanisms for both transmitted and stored information. One approach to enhance data confidentiality and efficiency is the combination of compression and data hiding techniques. This study aims to analyze the application of Huffman compression and Least Significant Bit (LSB) steganography for embedding text messages into digital images without developing a dedicated application. The text data were first compressed using the Huffman algorithm to reduce their size, and the resulting bitstream was embedded into an image using the LSB technique. The results indicate that Huffman compression successfully reduced data size by more than 80%, allowing the embedding process to be more efficient. The LSB method also demonstrated its ability to conceal messages without introducing noticeable visual distortion in the cover image. The combination of these methods provides an efficient data-hiding process while maintaining the visual quality of the media. This study highlights that compression and steganography techniques can serve as a simple yet effective approach for digital data protection.